Tourism Revisit and Recommendation intention on Heritage Destination: The Role of Memorable Tourism Experiences - Riptiono, Sulis; Wibawanto, Sigit; Raharjo, Nanang Ismail; Susanto, Rakhmat; Syaputri, Hani Shella; Bariyah, Bariyah (AIBPM Publisher, 2023)
The purpose of this study is to dig deeper into the role of memorable tourism experiences in revisiting intention and recommendation intention by placing tourism satisfaction as mediation. This research involved a number of 340 tourists visiting heritage destinations in Central Java. Respondents were taken using a convenience sampling technique. The collected data was analyzed by SEM-AMOS. The results of the study show that memorable tourism experiences are proven to have a positive and significant effect on tourist satisfaction. This means that the more memorable the experience the visitor gets, the greater the satisfaction increasing the intention to return and recommendation intention. Memorable experiences also significantly affected the intention to return and recommendation intention. Memorable experience and satisfaction are very important factors for tourists to determine their choice to visit heritage tourism destinations. Therefore, tourism managers must pay attention to cultural heritage sites so that tourists have a positive and unforgettable impression in their memories.Keywords: Heritage Destination, Revisit Intention, Recommendation, Satisfaction, Memorable Tourism Experiences